2006
DOI: 10.1038/modpathol.3800515
|View full text |Cite
|
Sign up to set email alerts
|

Precursors to melanoma and their mimics: nevi of special sites

Abstract: Melanocytic nevi, which are benign tumors of melanocytes, may have occasional cosmetic significance but, for the most part, they are important only in relation to melanoma. Nevi are the most important simulants of melanoma, both clinically and histologically, and can usually be reliably distinguished from melanomas using published criteria. Some lesions are characterized by greater degrees of atypia and may be more difficult to diagnose. Dysplastic nevi are among the most important simulants of melanoma. Nevi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(111 citation statements)
references
References 68 publications
7
100
1
3
Order By: Relevance
“…In the present study, among females the most common lesion was benign melanocytic nevi 17 (54.8%) which was similar to observations of Schafer et al 7 Nevi are benign melanocytic tumours that have cosmetic significance and may act as stimulants or precursors to melanoma. 8 In male's nevus sebaceous was most common lesion 5 (38.5%) which was similar to Rubegni et al, Rajesh et al 1,9 Majority of these lesions were situated on the face 29 (65.9%) and were similar to Rajesh et al In present study, it was observed that malignant melanoma was seen in 2 cases and both were females, which was comparable to other studies. 1,10 but dissimilar to the observations of KORA survey.melanoma is an aggressive tumour, its incidence in India is uncommon when compared to the West.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, among females the most common lesion was benign melanocytic nevi 17 (54.8%) which was similar to observations of Schafer et al 7 Nevi are benign melanocytic tumours that have cosmetic significance and may act as stimulants or precursors to melanoma. 8 In male's nevus sebaceous was most common lesion 5 (38.5%) which was similar to Rubegni et al, Rajesh et al 1,9 Majority of these lesions were situated on the face 29 (65.9%) and were similar to Rajesh et al In present study, it was observed that malignant melanoma was seen in 2 cases and both were females, which was comparable to other studies. 1,10 but dissimilar to the observations of KORA survey.melanoma is an aggressive tumour, its incidence in India is uncommon when compared to the West.…”
Section: Discussionsupporting
confidence: 81%
“…It is known for many years that a group of nevi in different anatomic sites that may simulate both dysplastic nevi and melanoma [1,6,7,12]. these nevi have been termed generically "nevi of special sites".…”
Section: Discussionmentioning
confidence: 99%
“…Nicolau Antonela-Anca 2 , Așchie Mariana 1,2 AbStrAct A large number of publications recognize that there are melanocytic lesions with microscopic features similar to melanoma, related to their location, with no prognostic importance. those locations are represented by the ear, the milk lines (axillary, breast, periumbilical and inguinal regions), palms, soles and flexural regions.…”
Section: Morphologic Analysis Of Periumbilical Nevimentioning
confidence: 99%
See 2 more Smart Citations